Microbial Electrosynthesis Inoculated with Anaerobic Granular Sludge and Carbon Cloth Electrodes Functionalized with Copper Nanoparticles for Conversion of CO2 to CH4 - Georgiou, Sofia G.; Koutsokeras, Loukas E.; Constantinou, Marios; Majzer, Rafał; Markiewicz, Justyna; Siedlecki, Marcin; Vyrides, Ioannis; Constantinides, Georgios (My University, 2022)
Microbial electrosynthesis (MES) can sustainably convert CO2 to products and significant research is currently being conducted towards this end, mainly in laboratory-scale studies. The high-cost ion exchange membrane, however, is one of the main reasons hindering the industrialization of MES. This study investigates the conversion of CO2 (as a sole external carbon source) to CH4 using membraneless MES inoculated with anaerobic granular sludge. Three types of electrodes were tested: carbon cloth (CC) and CC functionalized with Cu NPs, where Cu NPs were deposited for 15 and 45 min, respectively. During the MES experiment, which lasted for 144 days (six cycles), methane was consistently higher in the serum bottles with CC electrodes and applied voltage. The highest CH4 (around 46%) was found in the second cycle after 16 days. The system's performance declined during the following cycles; nevertheless, the CH4 composition was twice as high compared to the serum bottles without voltage. The MES with Cu NPs functionalized CC electrodes had a higher performance than the MES with plain CC electrodes. Microbial profile analysis showed that the Methanobacterium was the most dominant genus in all samples and it was found in higher abundance on the cathodes, followed by the anodes, and then in the suspended biomass. The genus Geobacter was identified only on the anodes regarding relative bacterial abundance at around 6-10%. Desulfovibrio was the most dominant genus in the cathodes; however, its relative abundance was significantly higher for the cathodes with Cu NPs.
Keywords: Anaerobic granular sludge; Microbial electrosynthesis; Carbon cloth electrodes; Copper nanoparticles